ANALISIS PENGARUH KOMPETENSI, LINGKUNGAN KERJA, DAN KOMPENSASI TERHADAP KEPUASAN KERJA DAN IMPLIKASINYA TERHADAP KINERJA APARATUR SIPIL NEGARA - Erni Aprida Hasibuan; Afrizal Afrizal (LPPM STIE PERTIBA Pangkalpinang, 2019)
This study aims to analyze the Effect of Work Environment Competence and Compensation on Job Satisfaction and examine the effect of job satisfaction. The number of samples used was 54 (fifty-four) State Civil Apparatus (ASN) in the Regional Office of the National Land Agency of the Bangka Belitung Islands Province. Data analysis method uses path analysis (Path analysis). The results of the study concluded that there was a significant influence on the competency, work environment and compensation variables on job satisfaction. Furthermore, for the variable job satisfaction, there is a positive influence on employee performance. Based on these results, the Regional Office of the National Land Agency of Bangka Belitung Province needs to increase job satisfaction through competence, work environment and compensation for future employee performance improvement.